Theoretical Study of Carbon Nanotube toward Adenine Sensing: DFT Study - Ahmed T. Khudhair; Falah H. Hanoon (University of Thi-Qar Journal of Science, 2021)
As a due of its electronic and physical properties, the carbon nanotube (CNT) is utilized in the production of accuracy sensors. In this paper, the thickness utilitarian hypothesis Density Functional Theory (DFT) with the B3LYP level, and by utilization of the Gaussian 09 arrangement of projects, were used to explore the adsorptive and detecting ability of Adenine on the unblemished CNT. The detecting capacity of these structures was determined as far as a variation of band hole vitality after cooperation among CNT and Adenine. Due to counts, it was found that the electronic properties of CNT are firmly delicate to the nearness of Adenine. In this way, we accept that GNRs can be utilized in sensor gadgets